2011
DOI: 10.1088/0953-8984/24/1/015901
|View full text |Cite
|
Sign up to set email alerts
|

Off-center displacements and hydrostatic pressure induced phase transition in perovskites

Abstract: Pressure has a profound effect on the paraelectric and ferroelectric properties of perovskite crystals. In this paper we theoretically investigate the effect of pressure on the cubic-to-tetragonal phase transition and on the soft mode dynamics of some classical perovskite crystals: BaTiO(3), PbTiO(3), and KNbO(3). We use a model consisting of three subsystems: electrons, phonons, and off-center displacements treated as spins. Experiments show that pressure has a large effect on the tunneling and hopping of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Many of the unique properties of perovskite-type materials are a result of local distortions and peculiar atomic dynamics in such materials. Importance of such effects as anisotropy and anharmonicity of atomic vibrations and the presence of strong correlations in atomic displacements is acknowledged, for instance, in many studies of phase-transitions [7,8,9], ferroelectric properties [7,10,11] and negative thermal expansion effect [12,13,14,15], observed in perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the unique properties of perovskite-type materials are a result of local distortions and peculiar atomic dynamics in such materials. Importance of such effects as anisotropy and anharmonicity of atomic vibrations and the presence of strong correlations in atomic displacements is acknowledged, for instance, in many studies of phase-transitions [7,8,9], ferroelectric properties [7,10,11] and negative thermal expansion effect [12,13,14,15], observed in perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, despite their importance, these relationships are only known for a very few specific cases of boundary conditions and are mostly limited to the soft mode dynamics under hydrostatic pressure. For example, in case of PbTiO 3 the dependence of the soft-mode frequency on the hydrostatic pressure has been studied quite extensively using both experimental [6][7][8][9] and theoretical approaches [10,11]. These studies revealed that in the tetragonal ferroelectric phase the frequency of the soft transverse optical mode, ν, can be well described by the Curie-Weiss pressure law ν 2 = A P (P − P 0 ) (1) where A P is the Curie-Weiss pressure constant, P is the hydrostatic pressure and P 0 is the pressure at which the mode frequency extrapolates to zero.…”
Section: Introductionmentioning
confidence: 99%